Gilbert-style Pleistocene fan delta reveals tectonic development of North Island axial ranges, New Zealand. Issue 1 (2nd January 2018) - Rees, Callum; Palmer, Julie; Palmer, Alan
ABSTRACT: A 66 m thick Pleistocene succession (Konewa Formation) exposed in southern Pohangina Valley, New Zealand, records predominantly coarse terrigenous clastic deposition in a wave-dominated fan delta and nearshore to offshore shallow marine environments. Depositional environments are interpreted from facies associations based on sedimentary features and biostratigraphy. The fan delta environment is characterised by sub-aerial to subaqueous, plastic or pseudoplastic, clast-rich debris flow deposits. These are consistent with debris flows initiated during partial collapse of steeply dipping, unstable delta foresets, and avalanching of sediment building up at the top of the delta system. The fan delta facies are interpreted to represent a Gilbert-style fan delta with a fluvial signature in beds deposited within the delta plain, steeply dipping foresets in the delta front, and a marine signature to beds deposited in the pro-delta zone. The Konewa Formation provides valuable insights into the potential connection between Whanganui Basin and Hawke's Bay, a region now separated by tectonic uplift forming the North Island axial ranges. Biostratigraphy of deposits associated with the prograding delta system places a potential phase of tectonic uplift in the northern Ruahine Range within early Nukumaruan time (c. 2.4 Ma).